Can genetics predict sports injury? The association of the genes GDF5, AMPD1, COL5A1 and IGF2 on soccer player injury occurrence - McCabe, K.; Collins, C. (Sports, 2018)
Genetics plays an integral role in athletic performance and is increasingly becoming recognised as an important risk factor for injury. Ankle and knee injuries are the most common injuries sustained by soccer players. Often these injuries result in players missing training and matches, which can incur significant costs to clubs. This study aimed to identify genotypes associated with ankle and knee injuries in soccer players and how these impacted the number of matches played. 289 soccer players, including 46 professional, 98 semi-professional and 145 amateur players, were genetically tested. Ankle and knee injuries and the number of matches played were recorded during the 2014/15 season. Four genes were assessed in relation to injury. Genotypes found to be associated with injury included the TT (nucleobase) genotype of the GDF5 gene, TT and CT (nucleobase) genotypes of AMPD1 gene, TT genotype of COL5A1 and GG (nucleobase) genotype of IGF2 gene. These genes were also associated with a decrease in the number of matches played.